Analisis Peranan Kartu Member Terhadap Minat Belanja di Indomaret - Marsella Wijaya; Rio Ferdinand; Gracielan Giani; Erich Priestly; Kelvin Kelvin (Institut Nalanda, 2024)
The aim of this study is to see how member cards influence shopping interests in Indomaret districts. This study analyzes the relationship between independent variables (user member card characteristics) and dependent variables. (minat belanja). As the results of the analysis show, there is a correlation between predictor variables related to member card usage and shopping interests. However, a low R-squared value, around 4.1%, suggests that the model cannot explain the variation of shopping interests well. It suggests that factors outside the model can influence the purchasing interest of member card users. The F-statistic value of 1,411 indicates that the overall statistical test of the model was successful; however, the F value must be compared with the relevant critical value to ensure the significance of the Model. Because the low level of explanation indicates the inability of the model to predict variations, the importance of careful interpretation is pointed out